Ways to improve the quality of drinking water Akmola region and measures for its improvement - Smagulova Эльмира; Mahauova Эльвира (Рroblems of engineering and professional education, 2023)
The article discusses the issues and methods of purification of drinking water of (Vyacheslavskii) in Astana, describes the main features, advantages and disadvantages